Multiparameter flow cytometry enables immune profiling and IFN pathway analysis in human minor salivary glands - Yamada, Eiko; Dominick, Kalie; Kulchar, Rachel J.; Twohig, Joseph; Khavandgar, Zohreh; Beach, Margaret; Pelayo, Eileen; Baer, Alan; Perez, Paola; Warner, Blake M. (Frontiers in Dental Medicine, 2025)
Aim/IntroductionWe aimed to achieve direct quantitative measurement of activated and therapeutically actionable pathways (e.g., Type-I interferon) in target organs of autoimmune disease using flow cytometry of human salivary glands. Sjögren's Disease (SjD) is a systemic autoimmune disorder characterized by lymphocytic inflammation and dysfunction of the lacrimal and salivary glands. Minor salivary glands are routinely biopsied and are used for the histopathological diagnosis of SjD. In this study, we optimized the dissociation, permeabilization, antibody panel, and analytical parameters to characterize both the immune and epithelial cells in the glands, and the activation status of a specified pathway by measuring intracellular phosphorylated proteins.MethodsFresh human MSG biopsies were dissociated into single-cell suspensions and permeabilized under optimized conditions. MSG suspensions were stained for cell surface and intracellular markers then analyzed using nine-color conventional flow cytometry, including two intracellular markers.ResultsOur optimized dissociation and permeabilization protocols for human MSG preserved key cell surface markers. Our flow cytometry panel identified major immune cell populations and distinguished epithelial cells via cytokeratin-18. We demonstrate the protocol's utility showing differential interferon pathway activity in SjD vs. healthy MSG leukocytes and epithelial cells. We provide guidance on panel selection, analytical capabilities, and the impact of cell yield on resolution using conventional flow cytometry.ConclusionOur optimized protocol enables high-resolution characterization of immune and epithelial cell populations in human MSG, preserving key markers and capturing interferon pathway activity. Our protocol provides a robust framework for the direct study of immune heterogeneity and signaling dynamics in SjD at single cell resolution.